(untitled) (International Journal of Engineering and Computer Science, 2018)
As the nodes in Ad Hoc network are battery limited the most important issue that must be considered in designing a data transmission algorithm for wireless Ad Hoc network is how to save energy while meeting needs of users. While satisfying energy requirement it is also necessary to achieve quality of service. Reliable Minimum Energy Routing (RMER) and Reliable Minimum Energy Cost Routing (RMECR) are two proposed routing algorithms which meets the requirements. RMER and RMECR ensure Energy efficiency and Reliability. RMECR considers residual energy of nodes while finding energy efficient path for data transmission thus RMECR along with Energy efficiency and Reliability also prolongs network lifetime. Simulation results mentioned in this paper show the performance comparison of RMER and RMECR based on the performance metrics Average Residual Energy, Reliability, Throughput